2016
DOI: 10.1038/srep33535
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of long non-coding RNA expression profiles in pancreatic ductal adenocarcinoma

Abstract: Pancreatic ductal adenocarcinoma (PDAC) remains one of the most aggressive and lethal malignancies. Long non-coding RNAs (lncRNAs) are a novel class of non-protein-coding transcripts that have been implicated in cancer biogenesis and prognosis. By repurposing microarray probes, we herein analysed the lncRNA expression profiles in two public PDAC microarray datasets and identified 34 dysregulated lncRNAs in PDAC. In addition, the expression of 6 selected lncRNAs was confirmed in Ren Ji cohort and pancreatic cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 55 publications
(76 reference statements)
2
48
0
4
Order By: Relevance
“…LncRNAs are nucleotidic chains exceeding 200 bases that are not translated into proteins. Besides regulating gene transcription at many levels, they are also specifically involved in the epigenetic regulation of DNA [44].…”
Section: Microrna and Long Non-coding Rnamentioning
confidence: 99%
See 1 more Smart Citation
“…LncRNAs are nucleotidic chains exceeding 200 bases that are not translated into proteins. Besides regulating gene transcription at many levels, they are also specifically involved in the epigenetic regulation of DNA [44].…”
Section: Microrna and Long Non-coding Rnamentioning
confidence: 99%
“…Many lncRNAs showed prognostic value, although the reproducibility of the results is controversial. The lncRNAs most consistently associated to shorter OS in www.oncotarget.com PDAC patients are MALAT1 [54-56], AFAP-AS1 [57,58,44] and UCA1 [44]. Overall, the individual prognostic value of each lncRNAs is too weak for direct clinical development, therefore more recently panels including analysis of the expression levels of up to 12 lncRNAs are being investigated for their prognostic value [59,60].…”
Section: Microrna and Long Non-coding Rnamentioning
confidence: 99%
“…At present, more and more evidence demonstrated that lncRNA played an important molecular role in apoptosis, proliferation, progression, metastasis, invasion, and relapse of the various tumor . Recent studies indicated that the dysregulated lncRNA expression profiles were associated with the development and survival in patients with various cancers, including PDCA, which uncovers the potential of lncRNA as prognostic cancer biomarker …”
Section: Introductionmentioning
confidence: 95%
“…No contexto do câncer pancreático, poucos estudos fizeram análises comparativas entre amostras tumorais (T) e normais (N) para identificação de lncRNAs associados a tumorigênese. Dois trabalhos utilizaram microarranjos de cDNA para analisar amostras T/N identificando perfis de expressão de lncRNAs associados com malignidade e metástase (Tahira et al 2011;Fu et al 2016) . Recentemente, Song e colaboradores exploraram dados de expressão de 178 amostras de PDAC e apenas 4 de tecido não tumoral de pâncreas e encontraram 5 lncRNAs com potencial como marcador prognóstico ( C9orf139 , MIR600HG , RP5-965G21.4 , RP11-436K8.1 , e CTC-327F10.4 ) (Song et al 2018) .…”
Section: I3 Rnas Não Codificadores Longos (Lncrnas)unclassified
“…Hu et al 2018) . Particularmente no câncer pancreático, poucos trabalhos em larga escala focaram na identificação de RNAs não codificadores com expressão desregulada no tumor em relação ao tecido pancreático não tumoral (Tahira et al 2011;Song et al 2018;Fu et al 2016;Mao et al 2017) , sendo que nenhum deles aplicou uma abordagem experimental que investigasse a fração não-poliadenilada no transcritoma.…”
Section: I5 Motivaçãounclassified